Characteristics of Nephrolithiasis Patients at Ulin General Hospital Banjarmasin 2017-2018 Period - Nazmyatus Sa’idah; Eka Yudha Rahman; Dewi Indah Noviana Pratiwi; Heru Prasetya; Siti Kaidah (Fakultas Kedokteran Universitas Lambung Mangkurat, 2021)
Abstract: The purpose of this study was to determine the characteristics of nephrolithiasis patients at Ulin General Hospital Banjarmasin based on sex, age, and residence place of patients. This study was conducted at Ulin General Hospital Banjarmasin, using a descriptive method with a retrospective approach. A total of 100 nephrolithiasis patients were obtained by total sampling according to inclusion and exclusion criteria. The results of this study showed that all nephrolithiasis patients in the 2017-2018 period were recorded, there were 58 male patients (58%), while there were 42 female patients (42%). The results showed that nephrolithiasis patients at Ulin General Hospital Banjarmasin were more than 55-64 years old (31%) and Banjarmasin was the area where most nephrolithiasis patients with a number of 35 patients (35%). This study showed the characteristics of age, sex, and residence place of patients were the risk factors that influence the incidence of nephrolithiasis at Ulin General Hospital Banjarmasin. Keywords: Patient Characteristics, Nephrolithiasis, Ulin General Hospital Banjarmasin.